Development of Panda Adventure Game to Enhance Eighth Graders’ Narrative Reading Comprehension - Saputra, Niko Andi; Sutanti, Nita; Primasari, Yusniarsi (JOSAR (Journal of Students Academic Research), 2025)
Reading comprehension is an essential skill in language learning, particularly for students studying English as a foreign language (EFL). However, many students struggle with understanding narrative texts due to limited vocabulary and a lack of engagement with traditional teaching methods. This study aims to develop and evaluate the effectiveness of the Panda Adventure Game, an interactive educational game designed to enhance students' reading comprehension of narrative texts. The research follows a Research and Development (R&D) approach, employing a modified version of Sugiyono’s model, which includes stages such as data collection, design and development, expert validation, teacher and student feedback, evaluation, and final product publication. The game was tested in three junior high schools: SMPN 1 Sutojayan, SMPN 2 Sutojayan, and SMPN 2 Panggungrejo. The results from expert validation indicate high validity, with material experts rating it at 97% and media experts at 96%. Additionally, teacher and student feedback suggest positive engagement, with 94% of teachers and 83.7% of students responding favorably. These findings suggest that the Panda Adventure Game is an effective alternative learning medium for teaching narrative texts, making reading comprehension more interactive and engaging for students. Future research could explore its implementation in broader contexts and its impact on different language skills.